Attack on Titan. 12 - Isayama, Hajime, 1986- (Kodansha Comics, 2014)
Erwin and the Survey Corps desperately mount a rescue operation to take Eren back from the Colssus Titan and Armored Titan. But without the numbers to form up properly outside the walls, how can the humans catch up before they're all slaughtered?